Alice’s Adventures In Wonderland: Parodies, Dialect and Personal Names in Slovene Translations (Preučevanje otroške in mladinske književnosti, 2025)
Lewis Carroll's brilliant satirical fantasy Alice's Adventures in Wonderland is among the most translated literary works in the world. The adventures of polite and curious Alice are available to Slovenian readers in five translations. The first translation with a modified title Alica v deveti deželi was prepared by Bogo Pregelj (1951), followed by the translations of Gitica Jakopin Alica v čudežni deželi (1969) and Aličine dogodivščine v čudežni deželi in v ogledalu (1990), Aličine prigode v čudežni deželi by Helena Biffio (1994) and the most contemporary translation Alica v čudežni deželi (2022) by Milan Dekleva. The paper focuses on the translation methods used to translate parodies of popular didactic songs in the Victorian era, Irish version of the English language, titles of school subjects and personal names of the main protagonists. The purpose of the analysis is to examine translation solutions and how they affect the reader's interpretation of Carroll's narrative.